2013
DOI: 10.1039/c3cc37987f
|View full text |Cite
|
Sign up to set email alerts
|

Achiral CdSe quantum dots exhibit optical activity in the visible region upon post-synthetic ligand exchange with d- or l-cysteine

Abstract: Semiconductor cadmium selenide (CdSe) quantum dots (QDs) exhibited mirror-image circular dichroism (CD) spectra in the visible region (350-570 nm) after replacing the trioctylphosphine oxide/oleic acid ligands on achiral nanocrystals with D- and L-cysteines. Chiroptical properties of cysteine-capped CdSe QDs depend on their size and can be fine-tuned by changing the radius of QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
97
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 28 publications
2
97
0
2
Order By: Relevance
“…Since then, the chiroptical behavior of QDs has been demonstrated for different ligand stabilizers (cysteine, glutathione), other semiconductors (CdSe and CdTe), different synthetic routes (solution phase techniques and ligand exchanged from its native achiral ligand to a chiral one), and different QD shapes (tetrapods, rods). 25,27,28,29,30,31,32,33 Here, chiral cysteine passivated CdSe QDs are synthesized and their spin dependent charge transport properties are measured using magnetic conductive probe atomic force microscopy (mCP-AFM) and magnetoresistance (MR) measurements. The findings from this 4 study show that the individual QDs and the QD films act as spin filters.…”
mentioning
confidence: 99%
“…Since then, the chiroptical behavior of QDs has been demonstrated for different ligand stabilizers (cysteine, glutathione), other semiconductors (CdSe and CdTe), different synthetic routes (solution phase techniques and ligand exchanged from its native achiral ligand to a chiral one), and different QD shapes (tetrapods, rods). 25,27,28,29,30,31,32,33 Here, chiral cysteine passivated CdSe QDs are synthesized and their spin dependent charge transport properties are measured using magnetic conductive probe atomic force microscopy (mCP-AFM) and magnetoresistance (MR) measurements. The findings from this 4 study show that the individual QDs and the QD films act as spin filters.…”
mentioning
confidence: 99%
“…Furthermore, most accounts in literature describe procedures providing electrostatic stabilization in basic conditions, and with negatively charged surfaces. [16][17][18][19]21,23,24,[26][27][28][29] The formation of nanocomposites however, may involve acidic matrix precursor solutions 6,7 whereas the uptake of nanoparticles by immune cells was found to be enhanced by positive surface charges. 30 Potentially useful procedures in this respect involve the use of stripping agents such as NOBF 4 , 31 RO 3 BF 4 , 32 and BF 3 33 which operate in acidic conditions, or dopamine, which stabilizes titania NCs by a positive surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfide or selenide based ligands for example, proved excellent for ligand exchange on metals and metal sulfides, selenides, phosphides or arsenides but showed little affinity towards oxide NCs. [15][16][17][18][19][20][21][22] In addition, ligand exchange schemes 19,[23][24][25] tend to use solvents with high dielectric constants (e.g., formamide, ε = 111 or N-methylformamide, ε = 180) that favor electrostatic stabilization. However, the application of those high-boiling, unstable and toxic solvents is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the area of chiral nanocrystals has received a great deal of attention due to the range of potential applications offered by these materials in chiral chemo-and bio-sensing, nano-bio interfaces, and spintronics. It has been demonstrated that optically active nanocrystals can be obtained by various methods [2][3][4][5][6][7][8][9][10][11][12][13][14]. Initially chiral Quantum Dots (QDs) have been prepared by using microwave induced heating with chiral ligand penicillamine as stabilizer [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%